The impact of film censorship and its relevance to young adults in Malaysia today - Chai, Yating (2023)
Throughout these years, film censorship in Malaysia is under control by the government of the Film Censorship Board of Malaysia (Lembaga Penapis Filem)- (LPF). However, the advancement of social networking becomes a challenge to the Malaysian Film Censorship Board by controlling the audience to watch any sensitive content such as homosexual, political, and religious content that is against the principles of LPF. Therefore, this research aims to examine the impact of film censorship and its relevance to young adults in Malaysia nowadays. The objective of this research is to examine the perspective of young adults on homosexual, political, and religious films in Malaysia, to identify the behavior of young adults towards film censorship in Malaysia, and to study the relevancy of film censorship to young adults in Malaysia today. Besides that, the cultivation theory was applied to this research to examine the relationship between the impact of film censorship and the effects of media that caused behavioral changes in young adults. This research was conducted with quantitative research by using the liking scale method and the questionnaire was distributed to the young adults who currently stay in Klang Valley. The data will be collected from the respondents for data analysis. The sample size of this research will be the number of 150 young adults between the age of 1826 who staying in Klang Valley. This survey will be carried out via google form to collect the data from the respondents. Therefore, the effect of film censorship and its relevancy to young adults in Malaysia today need to be further examined psychologically.